Does audit quality mediate the effect of information technology and competence on internal audit effectiveness? - Lonto, Miryam P.; Pandowo, Aditya (Jurnal Akuntansi dan Auditing Indonesia, 2025)
The effectiveness of the internal audit function plays a vital role in the government system’s detection of all fraud risks in an organization. Therefore, this study aims to examine the effects of information technology, competence and professional proficiency on the effectiveness of internal audits, with internal audit quality as a mediator. This study applies a quantitative approach involving a survey of the internal auditors of the Inspectorates of Greater North Sulawesi, the Financial and Development Supervisory Agency, and a census sampling technique. The results of the study show that the use of information technology increases the effectiveness of internal audits, and the higher audit quality resulting from auditor competence increases the effectiveness of internal audits. This study supports institutional theory, provides implications for regional inspectorates to maintain audit quality in performing their respective tasks, and strongly encourages the use of E-Audit applications for early fraud detection in local governments.